The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1111/j.1365-2672.1994.tb02818.x
|View full text |Cite
|
Sign up to set email alerts
|

Salvage synthesis of purine nucleotides by Helicobacter pylori

Abstract: The incorporation of purine nucleotide precursors into Helicobacter pylori and the activities of enzymes involved in nucleotide salvage biosynthetic pathways were investigated by radioactive tracer analysis and nuclear magnetic resonance spectroscopy. The organism took up the nucleobases adenine, guanine and hypoxanthine, and the nucleosides adenosine, guanosine and deoxyadenosine. Any incorporation of deoxyguanosine by the cells was below the detection limits of the methods employed. The activities of adenine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 23 publications
1
36
1
Order By: Relevance
“…11B). These results confirm the absence of adenosine kinase and guanosine kinase in H. pylori, as has been previously noted (1,16,50). Curiously, we found that the ⌬deoD mutant also was incapable of growth on the purine base adenine.…”
Section: Figsupporting
confidence: 77%
See 2 more Smart Citations
“…11B). These results confirm the absence of adenosine kinase and guanosine kinase in H. pylori, as has been previously noted (1,16,50). Curiously, we found that the ⌬deoD mutant also was incapable of growth on the purine base adenine.…”
Section: Figsupporting
confidence: 77%
“…Purine salvage and utilization have previously been examined in H. pylori (18,49,50). Radiolabeling studies have been used to show uptake and incorporation of the purine bases adenine and guanine (and to a lesser extent, hypoxanthine) (50).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This would allow H. pylori to surround itself with a perpetual nuclease cloud, which could aid not only in natural transformation, as has been previously shown (39,40), but also in the degradation of extracellular, host cell DNA. Once the DNA is broken down, purine bases can pass readily through the bacterium's porous outer membrane and subsequently be transported through the inner membrane by purine permeases, such as NupC, whose activity in H. pylori has been described previously in the literature (20,43).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it has been shown throughout the literature that the majority of laboratory/clinical strains of H. pylori grow best in vitro on the purine base adenine or hypoxanthine (14,15,(17)(18)(19)(20). Adenine is the most prominent purine in the blood (22), and of all the purine bases, it has been shown to be the most rapidly taken up and processed into nucleotides by H. pylori (43). All these findings, including the more recent discovery of adenosine deaminase activity in at least three H. pylori strains (16,17,20), have pointed to adenine/adenosine being the prominent purine base/nucleoside utilized by this bacterium.…”
Section: Discussionmentioning
confidence: 99%